Characterization of Oil Palm Trunk Composite for Application of Particle Board Using Urea-Formaldehyde as Binding Agent - Mohamad Afif Adis; Dalila Mohd Harun (Progress in Engineering Application and Technology, 2025)
This study investigates the development of sustainable particleboard from oil palm trunk (OPT) waste using urea-formaldehyde (UF) resin as a binder. OPT fibers (2-4mm) were chemically treated with 5% sodium hydroxide (NaOH) to enhance surface properties, then combined with UF resin at three different weight ratios (25:60, 25:65, and 25:70 OPT-to-UF). The composite mixtures were hot-pressed at 120°C under 5 MPa pressure for 30 minutes to form particleboards. Comprehensive testing revealed that increasing UF content significantly improved material properties, with the OPT25:70 formulation demonstrating optimal performance: highest density (1.20 g/cm³), lowest water absorption (40.44%), and superior mechanical strength (modulus of rupture: 412.87 MPa; modulus of elasticity: 62,339.21 MPa). The boards also showed improved dimensional stability, with thickness swelling decreasing to 27.50% for the highest resin content. These results confirm that properly processed OPT waste can produce particleboards meeting industrial standards, offering an eco-friendly alternative to conventional wood-based panels while effectively valorizing agricultural byproducts. The study provides important insights for sustainable material development in the wood composites industry.